PENGEMBANGAN MEDIA PEMBELAJARAN TEMATIK TERPADU BERBASIS MACROMEDIA FLASH 8 DI KELAS IV SD - Yolanda, Yola; Sri Lena, Mai (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2021)
This research intends to develop an integrated thematic learning media based on Macromedia Flash 8 in grade IV SD Negeri 02 Tanjuang Puan Abai which is valid, practical and effective. And apply ADDIE type. Subjects were fourth grade teachers at SDN 02 Tanjuang Puan Abai and 21 fourth grade students at SD Negeri 02 Tanjuang Puan Abai. The research revealed: (1) integrated thematic learning media based on Macromedia Flash 8 in grade IV SD which was validated by experts was declared "very valid" with an overall validator score of 87.87%, (2) teacher responses and student responses to learning media Thematically based on Macromedia Flash 8 in the fourth grade of SD obtained the "very practical" category with an assessment of 94.28% and 90.47%, (3) The response of the effectiveness of Macromedia Flash 8 students to the learning in the fourth grade of elementary school with the category "High â€ with a percentage of 87.21%.